Model Accountability And Transparency On Financial Management Nonlaba - Otniel Safkaur (Jurnal ASET (Akuntansi Riset), 2023)
This research aims to determine the policies and practices of Accountability, Transparency, Management and Accountability of Non-Profit Financial Institutions of the Evangelical Christian Church in Klasis Jayapura. Combined accountability and transparency in financial management and accountability systems are used as a theoretical framework. Data collection was carried out by distributing Google Form questionnaires and manual questionnaires to church congregation respondents as the primary data population. The test tools used in the analysis include Partial Least Square (PLS) and Structural Equation Modeling (SEM). The target population of 500 people gathered only 315 congregations of the Jayapura Classical Evangelical Christian Church, proving that the financial accountability and transparency system has an influence on Management and Accountability Finance. The accountability and transparency policies and practices carried out at GKI Klasis Jayapura are based on the Interpretation of Financial Accounting Standards (ISAK) Number 35, accountability and transparency of GKI financial management and accountability at Klasis Jayapura. The research results show that the financial accountability of GKI Klasis Jayapura uses a traditional approach and is not in accordance with ISAK 35 Accountability and Transparency which was developed so that it does not reflect management and accountability in accordance with accounting standards. Previous research used primary and secondary data on profit-oriented organizations, but the current research uses primary data that was distributed directly to church congregation respondents. The financial position, cash flow reports show that there is no responsibility, this is proven by the lack of transparency regarding financial management.